Analysis of the Implementation of Fiqh Principles and Ta'zir Sanctions for Violations of Contracts - Muhammad Najiyullah Firmansyah; Imroatul Azizah (Konsultan Jurnal Ilmiah Indonesia, 2026)
This abstract aims to analyze the integration of Islamic economic principles with law enforcement through a review of the Compilation of Islamic Economic Law (KHES) and Islamic Criminal Law. The main study lies in how Islamic jurisprudence (fiqh) principles function as a philosophical and operational basis in mitigating economic disputes. Using normative legal research methods, this article examines various contracts in KHES that often intersect with aspects of legal violations. The research findings show that Islamic jurisprudence principles such as